Langerin-expressing dendritic cells in human tissues are related to CD1c(+) dendritic cells and distinct from Langerhans cells and CD141(high) XCR1(+) dendritic cells - Bigley, Venetia (J Leukoc Biol, 2015)
Langerin is a C-type lectin expressed at high level by LCs of the epidermis. Langerin is also expressed by CD8(+)/CD103(+) XCR1(+) cross-presenting DCs of mice but is not found on the homologous human CD141(high) XCR1(+) myeloid DC. Here, we show that langerin is expressed at a low level on DCs isolated from dermis, lung, liver, and lymphoid tissue and that langerin(+) DCs are closely related to CD1c(+) myeloid DCs. They are distinguishable from LCs by the level of expression of CD1a, EpCAM, CD11b, CD11c, CD13, and CD33 and are found in tissues and tissue-draining LNs devoid of LCs. They are unrelated to CD141(high) XCR1(+) myeloid DCs, lacking the characteristic expression profile of cross-presenting DCs, conserved between mammalian species. Stem cell transplantation and DC deficiency models confirm that dermal langerin(+) DCs have an independent homeostasis to LCs. Langerin is not expressed by freshly isolated CD1c(+) blood DCs but is rapidly induced on CD1c(+) DCs by serum or TGF-β via an ALK-3-dependent pathway. These results show that langerin is expressed outside of the LC compartment of humans and highlight a species difference: langerin is expressed by the XCR1(+) "DC1" population of mice but is restricted to the CD1c(+) "DC2" population of humans (homologous to CD11b(+) DCs in the mouse).